2018
DOI: 10.1007/s10851-018-0814-0
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Invariant Analysis of Covariance Trajectories

Abstract: Statistical classification of actions in videos is mostly performed by extracting relevant features, particularly covariance features, from image frames and studying time series associated with temporal evolutions of these features. A natural mathematical representation of activity videos is in form of parameterized trajectories on the covariance manifold, i.e. the set of symmetric, positive-definite matrices (SPDMs). The variable execution-rates of actions implies variable parameterizations of the resulting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
(64 reference statements)
0
38
0
Order By: Relevance
“…In order to quantify differences in FCs, represented by covariance matrices, we need a metric structure on the manifold of covariance matrices or SPDMs. While there are several Riemannian structures in the literature [11,13,14], we use the one introduced in [11], since it has the advantage of having close forms for many necessary operations we need on the SPDM manifold, e.g., geodesic distance, parallel transport, exponential map, inverse exponential map. Zhang et al [11] also have demonstrated that this metric is superior over other metrics such as the log-Euclidean one [13] in analyzing dynamic FCs.…”
Section: B Riemannian Structure On Symmetric Positive-definite Matrimentioning
confidence: 99%
“…In order to quantify differences in FCs, represented by covariance matrices, we need a metric structure on the manifold of covariance matrices or SPDMs. While there are several Riemannian structures in the literature [11,13,14], we use the one introduced in [11], since it has the advantage of having close forms for many necessary operations we need on the SPDM manifold, e.g., geodesic distance, parallel transport, exponential map, inverse exponential map. Zhang et al [11] also have demonstrated that this metric is superior over other metrics such as the log-Euclidean one [13] in analyzing dynamic FCs.…”
Section: B Riemannian Structure On Symmetric Positive-definite Matrimentioning
confidence: 99%
“…The affine-invariant metric [2,8,3] and the polar-affine metric [12] are different but they both provide a Riemannian symmetric structure to the manifold of SPD matrices. Moreover, both claim to be very naturally introduced.…”
Section: Affine-invariant Versus Polar-affinementioning
confidence: 99%
“…This change of basis can prevent from numerical approximations of the differential but one must keep in mind that V = V ′ in general. This identification was already used for the polar-affine metric (f = pow 2 ) in [12] without explicitly mentioning.…”
Section: The Continuum Of Deformed-affine Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are several Riemannian structures used in the literature (including one in Pennec et al (2006)), we briefly summarize the idea used in this paper. More details can be found in Su et al (2012) and Zhang et al (2015).…”
Section: Riemannian Structure On Symmetric Positive-definite Matricesmentioning
confidence: 99%